Guidance and Counseling Implementation Through the Parenting Program in the Early Childhood Education Unit - Muhammad Yusuf (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2022)
Management Guidance and counseling for children's education can be done with various methods and approaches. One of the objectives of this research is to provide an overview of the implementation of guidance and counseling through parenting programs in schools. The parenting program in schools is a manifestation of the collaboration between teachers and parents in providing stimulus to children's development. The type of this research is field research with a descriptive qualitative approach. As for the data collection through observation with the manager. Furthermore, conducting interviews with teachers with parenting mentors, and documentation. Related to the results of research on guidance and counseling services by kindergarten managers, it illustrates that the parenting program held has a great impact on teacher competence, child development, as well as building ghiro to improve the quality of learning and the cooperation of parents and guardians of students.